Nuclear receptor DHR4 controls the timing of steroid hormone pulses during Drosophila development. - Qiuxiang Ou; Adam Magico; Kirst King-Jones (PLoS Biology, 2011)
In insects, precisely timed periodic pulses of the molting hormone ecdysone control major developmental transitions such as molts and metamorphosis. The synthesis and release of ecdysone, a steroid hormone, is itself controlled by PTTH (prothoracicotopic hormone). PTTH transcript levels oscillate with an 8 h rhythm, but its significance regarding the timing of ecdysone pulses is unclear. PTTH acts on its target tissue, the prothoracic gland (PG), by activating the Ras/Raf/ERK pathway through its receptor Torso, however direct targets of this pathway have yet to be identified. Here, we demonstrate that Drosophila Hormone Receptor 4 (DHR4), a nuclear receptor, is a key target of the PTTH pathway and establishes temporal boundaries by terminating ecdysone pulses. Specifically, we show that DHR4 oscillates between the nucleus and cytoplasm of PG cells, and that the protein is absent from PG nuclei at developmental times when low titer ecdysone pulses occur. This oscillatory behavior is blocked when PTTH or torso function is abolished, resulting in nuclear accumulation of DHR4, while hyperactivating the PTTH pathway results in cytoplasmic retention of the protein. Increasing DHR4 levels in the PG can delay or arrest development. In contrast, reducing DHR4 function in the PG triggers accelerated development, which is caused by precocious ecdysone signaling due to a failure to repress ecdysone pulses. Finally, we show that DHR4 negatively regulates the expression of a hitherto uncharacterized cytochrome P450 gene, Cyp6t3. Disruption of Cyp6t3 function causes low ecdysteroid titers and results in heterochronic phenotypes and molting defects, indicating a novel role in the ecdysone biosynthesis pathway. We propose a model whereby nuclear DHR4 controls the duration of ecdysone pulses by negatively regulating ecdysone biosynthesis through repression of Cyp6t3, and that this repressive function is temporarily overturned via the PTTH pathway by removing DHR4 from the nuclear compartment.